Editorial preface of special issue: legal and contractual issues of Islamic banking and finance in the era of industry revolution - Hassan, Rusni; Mohd. Zain, Nor Razinah (International Journal of Management and Applied Research (IJMAR), 2019)
Islamic finance is an unavoidable phenomenon in the world financial system. Not only does it offer a new group of potential investors looking to diversify away from traditional investments but its responsive adaptation to economic and financial expectations are among the factors pushing its growth. The world’s financial markets are picking up on its potential and benefits. Countries are adopting Islamic finance into their jurisdictions by adding it into their legal and regulatory frameworks. With the continued expansion of Islamic finance, the vital role of a strong legal and Shariah framework in the sustainable development of Islamic finance has been extensively discussed. The rapid transformation of the functioning of the Islamic financial system must be accompanied by guarantees that the regulatory and legal framework is aligned with these developments. This is indeed an important subject, particularly in the present era; the Fourth Industrial Revolution (4IR). Islamic financial institutions have to move fast to reap the benefits of the 4IR and to maintain their relevance. The theme of this special issue is the legal and Shariah issues in Islamic finance in facing the challenges of 4IR. The contributions are mainly from the IIUM Institute of Islamic Banking and Finance (IIiBF) of the International Islamic University Malaysia which is a centre of excellence for education and research in Islamic banking and finance. As the preeminent IBF (Islamic Banking and Finance) research centre, IIiBF has produced numerous research and publications on related disciplines in Islamic banking and finance.